Human endogenous retroviruses in viral disease and therapy - Yian Li; Tianjiao Fan; Jie Cui (Wiley, 2022)
Abstract As retained sequences of ancient retroviruses, human endogenous retroviruses (HERVs) are widespread in the human genome. Although most HERVs have been inert throughout evolution, several HERVs are still functional and involved in various diseases, such as autoimmune diseases, cancer, neurological diseases and viral infection. Hence, certain types of therapies targeting HERVs or utilizing HERV tools have been developed. Here, we summarize recent findings on the role of HERVs in viral infection, including HERV dysregulation in different kinds of viral infections and the potential mechanisms of HERV‐mediated antiviral immunity. In addition, we provide an overview of HERV‐related therapies that directly target HERVs or are indirectly based on HERVs to improve the efficacy of vaccines and drugs.